Deep-sea Ophiuroidea (Echinodermata) collected during the TALUD cruises in western Mexico - Granja-Fernández, Rebeca; Hendrickx, Michel E.; Rangel-Solís, Pedro Diego; López-Pérez, Andrés (Zootaxa, 2023)
Deep-sea ophiuroids from western Mexico have been documented since 1899, but mostly by non-Mexican expeditions. TALUD is a Mexican project designed to study the deep-sea fauna from Mexico. As part of it, the present contribution provides for the first time detailed information about the taxonomy and distribution, as well as images, of deep-sea ophiuroids from western Mexico, representing a useful taxonomic identification tool for Ophiuroidea from the eastern Pacific. A total of 38 species of ophiuroid (35 identified at species level, one at genus level, and two as confer) were collected from 83 stations located at 123‒2,309 m depth. At a regional scale, several new species records are presented: six for western Baja California, five for western Baja California Sur, two for the Gulf of California, four for Jalisco, 14 for Colima, and five for Guerrero. Geographic (six) and bathymetric (seven) distribution ranges of species are extended. An updated list of deep-sea ophiuroids (61 species) from western Mexico is provided together with an identification key to species collected during this survey. In addition, nine records of deep-sea ophiuroids for the Mexican Pacific are unproven, doubtful or invalid. We corroborated the presence of Ophiacantha eurypoma and Ophiacantha pacifica in the study area and added Amphiura gymnogastra as the first record for Mexico. We propose to transfer Ophiacantha phragma to Ophiolimna on account of it having both granules and spines on the dorsal disc and striated arm plates. TALUD cruises collected 57 % of the total deep-sea species known to occur off Mexico, making it the most important survey of deep-sea Ophiuroidea carried out in western Mexico to date.